2008
DOI: 10.1002/pmic.200700925
|View full text |Cite
|
Sign up to set email alerts
|

ClpL is essential for induction of thermotolerance and is potentially part of the HrcA regulon in Lactobacillus gasseri

Abstract: Stress-inducible proteins are likely to contribute to the survival and activity of probiotic bacteria during industrial processes and in the gastrointestinal tract. The recently published genome sequence of probiotic Lactobacillus gasseri ATCC 33323 suggests the presence of ClpC, ClpE, ClpL, and ClpX from the Clp ATPase family of stress proteins. The heat-shock response of L. gasseri was studied using 2-D DIGE. A total of 20 protein spots showing significant (p<0.05) increase in abundance after 30 min heat-sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 57 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…ClpL is a heat shock protein found mainly in Gram-positive bacteria (16). Although the detailed functional studies on ClpL have been limited, several previous reports have shown that the protein plays an important role as a chaperone during heat shock (32,41,42,44). The protein was previously reported to be part of the CtsR regulon in several Gram-positive bacteria, such as Streptococcus thermophilus and Oenococcus oeni (18,44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ClpL is a heat shock protein found mainly in Gram-positive bacteria (16). Although the detailed functional studies on ClpL have been limited, several previous reports have shown that the protein plays an important role as a chaperone during heat shock (32,41,42,44). The protein was previously reported to be part of the CtsR regulon in several Gram-positive bacteria, such as Streptococcus thermophilus and Oenococcus oeni (18,44).…”
Section: Resultsmentioning
confidence: 99%
“…ClpL has never been reported to be involved in a specific protein degradation process. ClpL belongs to the HSP100/Clp ATPase family and has been shown to be important for the stress tolerance response in some organisms (15,41,42,45). Apart from its putative chaperone function and involvement in stress tolerance, very little is known about ClpL ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is found strictly in Gram-positive bacteria, including streptococci, and is involved in various cellular processes, such as the stress tolerance response, virulence, long-term cell survival, and antibiotic resistance (7,(30)(31)(32). Despite its importance, very little is known about the molecular functions of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…In Streptococcus pneumoniae, a respiratory pathogen, ClpL has been shown to be involved in thermotolerance, acid tolerance, virulence regulation, and resistance to various antibiotics that target the cell wall (29)(30)(31)(32).…”
mentioning
confidence: 99%